Crafting character : the architectural practice of CHYBIK + KRISTOF - Madlener, Adrian (Frame Publishers, 2023)
How can the discipline of architecture be used as a human-centered practice? Crafting Character presents architecture as a spatial dialogue and an exchange between character and audience, book and reader, building and city in a series of fourteen cinematic vignettes. Fourteen cinematic vignettes highlight projects as personified characters that have their own histories, dreams, secrets and stories to tell. Each vignette emphasizes this relational culture and the practice of Chybik + Kristof in working with the common bonds within a space as being more important than any individual arguments and divisions within it. The first monograph of the Brno-based studio, this volume marks an exciting collaboration between Chybik + Kristof, Lukas Kijonka and ExLovers Studio, Adrian Madlener and Frame Publishers. With a passion for experimentation from all parties, the resulting pages stand apart from traditional monographs. From the design to the prose, the values of relationality and human-centric approaches are imbued in the pages, creating a cinematic reference guide to the practice of Chybik + Kristof.